Multi-Stakeholder Platforms for Integrated Water Management. - Warner, Jeroen (Ashgate studies in environmental policy and practice., 2007)
As they provide a negotiating space for a diversity of interests, Multi-Stakeholder Platforms (MSPs) are an increasingly popular mode of involving civil society in resource management decisions. Illustrated by a wide geographical range of case studies, this book focuses on water management to take a positive, if critical, look at this phenomenon.